2021
DOI: 10.1177/23247096211022186
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Receptor Positive/HER2 Negative Breast Cancer With Isolated Bladder Metastasis: A Rare Case

Abstract: Breast cancer is the most common cancer diagnosed in women in North America. Hormone receptor positive (HR+) and HER2 negative (HER2−) breast cancers account for at least 60% to 70% of all breast cancer cases. They usually metastasize to lymph nodes, bones, liver, lungs, and brain. Urinary bladder is a very unusual site for metastatic HR+/HER2− breast cancer and occurs in only 2% of all metastatic disease. In this article, we present a case of a 63-year-old female with locally advanced breast cancer who underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Four (2.4%) of the 167 included cases with primary breast cancer had UB metastasis. Since then, there had been few reported cases, and was mostly due to local extension [ [8] , [9] , [10] ]. In a retrospective study of 6289 bladder tumors, 282 (4.5%) were characterized as secondary metastases and 7 (2.5%) of them were of primary breast origin; majority (n = 6, 85.7%) were detected only on post-mortem examination [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Four (2.4%) of the 167 included cases with primary breast cancer had UB metastasis. Since then, there had been few reported cases, and was mostly due to local extension [ [8] , [9] , [10] ]. In a retrospective study of 6289 bladder tumors, 282 (4.5%) were characterized as secondary metastases and 7 (2.5%) of them were of primary breast origin; majority (n = 6, 85.7%) were detected only on post-mortem examination [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Prior autopsy studies have shown that breast cancer invades bladders “outside-in”– involving the outer bladder wall with inward invasion through the detrusor muscle. 3 The mucosa is involved last. 2 , 3 Irritative symptoms, including incontinence, and frequency typically arise first and are indicative of detrusor involvement.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The mucosa is involved last. 2 , 3 Irritative symptoms, including incontinence, and frequency typically arise first and are indicative of detrusor involvement. 2 Involvement of the mucosa, and the associated symptom of hematuria, is often a late finding and explains why cytology is often benign.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations